BOARD CHARACTERISTICS AND FIRM PERFORMANCE: EMPIRICAL EVIDENCE FROM TURKEY - Mohammed, Nishtiman H. (Journal of Duhok University, 2018)
The objective of this study is to examines the relationship between board characteristics and firm performance. The study used data of 146 public listed firms in Istanbul stock exchange for the period of 2011-2015. The study utilised cross sectional time-series feasible generalized least squire regression, which count for autocorrelation and heteroscedasticity to examine the influence of board characteristics in firm performance in Turkey. This study results reflect that board attributes proxies by interlocking directorship, education level and board size improve firm performance. This study finds insignificant relationship between independent directors and firm performance. The finding of this study has policy and practical implication on corporate governance. For example, future regulation reforms might consider board attributes instead of the concentrate on more independent directors to work in the board of directors.